Hospital Antibiotic Wasting and Evaluation of Potential Ecologic Effects - Russell F Mankes; Charles D Silver (Annals of Environmental Science and Toxicology - Peertechz Publications, 2016)
Drugs in wastewater arise from direct disposal by healthcare facilities among many other sources. We report the wasting of antibiotics (Ab) dispensed at 2 hospitals in Albany, NY during a 2 year period. We consider drug metabolism, excretion, disposal and toxicity to aquatic organisms in strategies for reducing antibiotic waste and impacts on bacterial resistance. Drug records (12,345) from August, 2008 through April, 2009 included: numbers of drugs dispensed, returned and wasted. Overall, 77 kg of Ab were dispensed but only 1.3 kg were wasted. Six Ab (bacitracin, cefazolin, ceftriaxone, clindamycin, levofloxacin and vancomycin) accounted for 85% (66 kg) of drug dispensed; vancomycin (22 kg) was the most dispensed. Drug wasting as a percent of drug dispensed averaged 1.7% but varied widely. Almost one-half (45%) of the polymyxin B dispensed as a topical ointment was wasted or discarded. Only about 1.6% of vancomycin dispensed was wasted or discarded. None of the top 4 wasted and only 3 of the top 6 dispensed Ab had Persistence, Bioaccumulation and Toxicity (PBT) Index values or environmental risk ratio (PEC/PNEC) data available. Vancomycin was minimally toxic to invertebrates, fish or green algae. Bacitracin was the most toxic to invertebrates or fish. Cefazolin was essentially non-toxic to green algae. All of the wasted, discarded or dispensed Ab were excreted as parent compound in the urine and or feces of human patients at levels of 10 - 100% of the administered dose. In healthcare facilities, Ab are disposed by wasting into water or other receptacles. We recommend returning excess drugs to the hospital pharmacy for incineration as the recommended method of disposal. Ab use and dispensing should be monitored according to recognized guidelines of antimicrobial stewardship. Knowledge of the adverse impacts from the release of highly toxic drugs into the environment must influence Ab selection and disposal.